Anomalous Origin of Left Coronary Artery from Pulmonary Trunk in an Adult Patient A Rare Occurrence (Cardiovascular Journal, 2011)
Anomalous origin of coronary arteries is a rare cause of cardiac disease. One of the very rare coronary anomalies is origin of left main coronary artery from pulmonary trunk. Most of these patients die in the first year of life and only 10-15% survive in adulthood. We are reporting a rare case of anomalous origin of left coronary artery from pulmonary artery who survives into sixth decade of life. Key words: Anomalous origin of coronary artery, Pulmonary artery, Left coronary artery DOI: http://dx.doi.org/10.3329/cardio.v1i1.8209 Cardiovasc. j. 2008; 1(1) : 117-121